DIFUSI INOVASI ENZIM PAPAIN TERHADAP MINAT ANGGOTA KELOMPOK PEMBUDIDAYA IKAN (POKDAKAN) SUMBER SARI MAKMUR DI KECAMATAN LOA KULU KABUPATEN KUTAI KARTANEGARA - Ni'matul Udzma; Gusti Haqiqiansyah; Komsanah Sukarti (2339-1324, 2018)
The purpose of this research were determined the influence factors of readability, the classified level of readability, the correlation of respondent characteristic, the elements of communication, and also the characteristic of innovation of readability of Pokdakan members in Sumber Sari Makmur. This research was conducted since January to February 2017 in Sumber Sari Village, Loa Kulu, Kutai Kartanegara. The sampling method was used census to 11 respondent. The data was collected by observation, questionnaire and interview also it was analyzed by likert scale for the class interval continuing by Rank Spearman correlation with IBM SPSS Statistics 20. The result was obtained the influence factors of readability are the elements of communication and characteristics of innovation. That factors had significant correlation. The significant element of communication were described in source, message, and channel. The significant characteristics of innovation were relative advantage, compability and complexity. Thus, the level of readability of Pokdakan Sumber Sari Makmur members is 81.82% as showed as high and 18.18% as showed as moderate category.